2020
DOI: 10.1017/s0007114520004183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementing palmitic acid and altering the dietary ratio of n-6:n-3 fatty acids in low-fibre diets on production responses of dairy cows

Abstract: Supplementing palmitic acid (C16:0) in combination with modifying the dietary n-6/n-3 fatty acids (FA) ratio may benefit energy metabolism and milk responses of dairy cows. Twelve Holstein cows (70±11 days in milk) were used in a replicated 4×4 Latin square, and allocated to 4 low-fibre diets (18.5% forage neutral detergent fibre) supplemented with no FA (CON), or 2.4% C16:0-enriched supplement (PAL), 2.4% mixture (2:1) of C16:0 and n-6 FA (PW6), and mixture (2:1) of C16:0 and n-3 FA (PW3). The dietary ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(143 reference statements)
1
7
0
Order By: Relevance
“…Nevertheless, the study results concur with previous reports, in which high-forage diets supplemented with oil enriched with n-6 PUFAs (soybean oil) interfered with ruminal fermentation in dairy cows [54]; on the other hand, oil enriched with n-3 PUFAs (flaxseed oil) [53] and saturated FAs (palm oil) [52] had no effects on ruminal pH and total VFAs, respectively. Notably, the acetate to propionate ratio was not affected by any of the dietary treatments, which concurred with another study demonstrating that the FA type did not affect the acetate to propionate ratio in the rumen [55].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the study results concur with previous reports, in which high-forage diets supplemented with oil enriched with n-6 PUFAs (soybean oil) interfered with ruminal fermentation in dairy cows [54]; on the other hand, oil enriched with n-3 PUFAs (flaxseed oil) [53] and saturated FAs (palm oil) [52] had no effects on ruminal pH and total VFAs, respectively. Notably, the acetate to propionate ratio was not affected by any of the dietary treatments, which concurred with another study demonstrating that the FA type did not affect the acetate to propionate ratio in the rumen [55].…”
Section: Discussionsupporting
confidence: 90%
“…Many types of evidence showed that the immune system was impared during the transition period, including decreased mitogen-induced proliferation of lymphocytes, decreased antibody response, and decreased capacity of neutrophils to kill pathogens ( 5 ). One strategy to improve the metabolic status of transition cows is supplementing fatty acids (FAs), which can increase dietary energy density ( 6 , 7 ) and modulate the immune cell function and inflammatory response ( 8 ). Fatty acids can modify the immune response in several pathways, which include the inhibition of arachidonic acid metabolism, induction of anti-inflammatory mediators, modification of intracellular lipids, and activation of nuclear receptors ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their metabolisms are based on the same enzymes, which makes them competitive. There is evidence that higher concentration of n-6 PUFAs diet could result in lower conversion rate of ALA, and conversely, high concentrations of ALA could also reduce conversion of n-6 PUFAs (17)(18)(19). In light of this, numerous studies have revealed that the ratio of n-3/n-6 is closely related to body health, which again highlights the importance of the ratio of healthy dietary intake.…”
Section: In Vivomentioning
confidence: 99%